Editorial. Issue 11 (November 2017) - Mansfield-Devine, Steve
Abstract : Attacks on European Union countries are to be treated as acts of war, according to a new diplomatic statement that is currently in draft form. This is not an original stance to take, but the move does reflect the growing concern about the impact of hacking on economies and political processes.